Primary Dedifferentiated Amelanotic Anorectal Melanoma: Report of a Rare Case. (December 2019) - Bell, Phoenix D.; Israel, Anna-Karoline; Dunn, Andrew L.; Liao, Xiaoyan
Anorectal melanoma (ARM) is an uncommon aggressive malignancy that comprises 0.5% to 1.6% of all melanoma manifestations. Dedifferentiated melanoma is very rare with loss of all melanocytic differentiation markers and is usually seen in metastatic melanoma of cutaneous origin. In this article, we report the first case of primary dedifferentiated amelanotic ARM in a 68-year-old male who presented with anal discomfort that was initially treated as inflamed hemorrhoids. Physical examination revealed a large protruding anal mass, biopsy of which showed biphasic malignant tumor cells with distinct immunoprofiles: a superficial spindled/sarcomatoid component positive for SOX10 and S100, and a deeper epithelioid/rhabdoid component positive for desmin, AE1/AE3, and EMA. Both components were negative for HMB-45, Melan-A/MART-1, c-Kit, and other lineage markers. Molecular analysis by polymerase chain reaction demonstrated wild-type BRAF and KRAS genes. A diagnosis of dedifferentiated ARM was made based on the coexistence of a differentiated component (spindled: S100 and SOX10 positive) and a dedifferentiated component (epithelioid: all melanoma markers including S100 and SOX10 negative). Shortly afterwards, the patient developed extensive pulmonary and liver metastases and expired 20 days after the diagnosis was rendered, reinforcing the highly aggressive nature of this disease entity.